2017
DOI: 10.1038/s41598-017-14221-2
|View full text |Cite
|
Sign up to set email alerts
|

A chloroquine-induced macrophage-preconditioning strategy for improved nanodelivery

Abstract: Site-specific localization is critical for improving the therapeutic efficacy and safety of drugs. Nanoparticles have emerged as promising tools for localized drug delivery. However, over 90% of systemically injected nanocarriers typically accumulate in the liver and spleen due to resident macrophages that form the mononuclear phagocyte system. In this study, the clinically approved antimalarial agent chloroquine was shown to reduce nanoparticle uptake in macrophages by suppressing endocytosis. Pretreatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 77 publications
2
123
0
Order By: Relevance
“…In this study, the potential protective effects of BiNPs against apoptotic (ethanol) and oxidative stress‐inducing (hydrogen peroxide) agents were assessed. Macrophages were chosen as an in vitro model of cell stress as the largest portion of intravenously administered nanoparticles (synthetic or biological) are internalized by circulating or resident macrophages 1,41–44. Moreover, macrophages play a major role in tissue regeneration and several studies have demonstrated that the depletion of these cells causes impaired tissue repair 45,46.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the potential protective effects of BiNPs against apoptotic (ethanol) and oxidative stress‐inducing (hydrogen peroxide) agents were assessed. Macrophages were chosen as an in vitro model of cell stress as the largest portion of intravenously administered nanoparticles (synthetic or biological) are internalized by circulating or resident macrophages 1,41–44. Moreover, macrophages play a major role in tissue regeneration and several studies have demonstrated that the depletion of these cells causes impaired tissue repair 45,46.…”
Section: Resultsmentioning
confidence: 99%
“…Kupffer cells are the macrophages with the strongest phagocytic capacity. Pretreatment of mice with chloroquine before administering NPs provided a straightforward approach to reduce the uptake by macrophages . Before administration of drug‐carrying NPs, consumption of the phagocytic ability of Kupffer cells by over‐injection of blank NPs sounds reasonable .…”
Section: Strategies To Reduce Np Uptake By the Mpsmentioning
confidence: 99%
“…67,68 As a gene delivery enhancing agent, chloroquine's ability to promote endolysosome escape has long been recognized. [69][70][71] Chloroquine can rapidly diffuse into cells where it can be trapped in endolysosomes, 72 and upon protonation and subsequent influx of water molecules, chloroquine can induce osmotic swelling of the endolysosome and endolysosome leakage. 73,74 Thus, we used chloroquine as a positive control for endolysosome leakage and determine the extent to which blocking TPCs affects endolysosome leakage.…”
Section: Tpcs Are Involved In Tat Endolysosome Escapementioning
confidence: 99%